MECHANISMS FOR DEVELOPING METHODOLOGICAL TRAINING OF FUTURE INFORMATICS TEACHERS - Abduqodirov Elbek Abduvali o'g'li,Qurbonova Durdona G'olibjon qizi,Asqarova O'g& (International Journal of Literature and Language Studies, 2026)
The present study investigates the mechanisms for developing methodological training of future informatics teachers within the system of higher pedagogical education. The research identifies the structural components of methodological competence, examines existing barriers in the preparation process, and proposes a set of coherent mechanisms aimed at enhancing future teachers' readiness to design and deliver high-quality informatics instruction. The mechanisms examined include curriculum restructuring based on competency frameworks, mentoring and reflective practice systems, interdisciplinary collaboration, digital portfolio assessment, and continuous professional development cycles. An experimental study conducted at Namangan State University with 68 student-teachers confirmed that systematic implementation of the proposed mechanisms significantly improves methodological competence indicators compared to conventional preparation approaches. The findings contribute to the broader discourse on teacher education reform in Uzbekistan and offer practical implications for curriculum designers and faculty in pedagogical institutions.